Plasticizer for controlling single‐walled carbon nanotube fibers and zincophilic sites of microfiber supercapacitor. (10th July 2022) - Kim, Hyun‐Woo; Jin, Jeong‐Un; Lee, Dongju; Kim, Seo Gyun; Ku, Bon‐Cheol; Ryu, Seongwoo; You, Nam‐Ho
Summary: In the past few decades, single‐walled carbon nanotube (SWCNT) fibers have been considered for various applications, from aerospace to electronics including flexible devices. Here, we report an effective way of controlling the viscosity of the liquid crystal SWCNT phases for fiber spinning. By applying Tris(hydroxymethyl)aminomethane (THA)‐functionalization to single‐walled carbon nanotubes (SWCNT_CONH), we enhanced the free volume of individual SWCNTs, which synergistically affected the formation of nematic liquid crystal phases. As a result, we were able to precisely control the viscosity and phase transformation of the nematic liquid crystal phases for fiber spinning. The SWCNT fiber spun from those nematic phases with plasticizer (BP30CONH5; 30 mg/mL of SWCNT_BP with 5 wt% of SWCNT_CONH) exhibited noticeably higher mechanical properties (tensile strength, 1.44 GPa and tensile modulus, 169 GPa) with higher electrical conductivity (1899 S m 2 /kg). These fibers were also exceptionally flexible and showed endurable performance as wearable and flexible electronic electrode devices from well‐distributed zincophilic sites (CONH). As an Zn‐ion supercapacitor, the SWCNT fiber exhibited linear and volumetric capacitances of 14.33 mF cm −1 and 22.55 F cm −3 at 0.1 mA cm −1 with capacitance retention of 98% after over 30 000 bending tests. Abstract : Here, we report Tris(hydroxymethyl)aminomethane (THA)‐functionalization to single‐walled carbon nanotubes (SWCNTs) that control the viscosity of the liquid crystal SWCNTs phases for fiber spinning. Enhancement in the free volume of individual SWCNTs affected the formation of nematic liquid crystal phases. The spunned SWCNT fiber with plasticizer exhibited noticeably higher mechanical properties (tensile strength, 1.44 GPa and tensile modulus, 169 GPa) with higher electrical conductivity (1899 S m 2 /kg). Also, the SWCNT fiber was suitable for zinc‐ion supercapacitor from nitrogen functional group for zincophilic site.